2022
DOI: 10.3389/fnetp.2022.910862
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in Multiplex Leaky Integrate-and-Fire Networks With Nonlocal Interactions

Abstract: We study synchronization phenomena in a multiplex network composed of two rings with identical Leaky Integrate-and-Fire (LIF) oscillators located on the nodes of the rings. Within each ring the LIF oscillators interact nonlocally, while between rings there are one-to-one inter-ring interactions. This structure is motivated by the observed connectivity between the two hemispheres of the brain: within each hemisphere the various brain regions interact with neighboring regions, while across hemispheres each regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The majority of these models focuses on seizure dynamics (initiation, spread, termination) only, and the network character of the disease is only rarely taken into account ( Kalitzin et al, 2019 ; Goodfellow et al, 2022 ). Seizure-like events (states of synchronous rhythmic activity), however, may also emerge spontaneously—i.e., without a change in control parameters—from an oscillator network with some balance between regular and random topology ( Rothkegel and Lehnertz, 2014 ; Ansmann et al, 2016 ; Gerster et al, 2020 ; Anesiadis and Provata, 2022 ; Wu et al, 2022 ). Other mechanisms behind tipping phenomena include noise-, rate-, and shock-induced tipping [see, e.g., Ashwin et al (2012) ; Feudel et al (2018) ; Ritchie et al (2023) ; Swierczek-Jereczek et al (2023) ].…”
Section: Current Limitations and Potential Prospectsmentioning
confidence: 99%
“…The majority of these models focuses on seizure dynamics (initiation, spread, termination) only, and the network character of the disease is only rarely taken into account ( Kalitzin et al, 2019 ; Goodfellow et al, 2022 ). Seizure-like events (states of synchronous rhythmic activity), however, may also emerge spontaneously—i.e., without a change in control parameters—from an oscillator network with some balance between regular and random topology ( Rothkegel and Lehnertz, 2014 ; Ansmann et al, 2016 ; Gerster et al, 2020 ; Anesiadis and Provata, 2022 ; Wu et al, 2022 ). Other mechanisms behind tipping phenomena include noise-, rate-, and shock-induced tipping [see, e.g., Ashwin et al (2012) ; Feudel et al (2018) ; Ritchie et al (2023) ; Swierczek-Jereczek et al (2023) ].…”
Section: Current Limitations and Potential Prospectsmentioning
confidence: 99%
“…The study of chimera states in multilayer networks showed from early on that couplings between network layers can induce or destabilize chimera states in individual layers [7][8][9][10][11][12][13]19,[21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from ring networks [6][7][8][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28][29] , two-dimensional lattices [30][31][32] with a multiplex inter-layer coupling were analyzed. Further studies addressed the role of coupling delays 12,[22][23][24][25] , inter-layer couplings with temporal fluctuations 10,27 , of limited duration 26 , and with nonlinear inertia 9 , as well as intra-layer coupling strengths adapting to the phase difference of interacting oscillators 21,33 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations